ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA PENOLAKAN SUATU KLAIM NASABAH ASURANSI (STUDI KASUS PADA ASURANSI JIWA SYARIAH BUMIPUTERA KANTOR PEMASARAN MEDAN) - Dwita Fratiwi; Fauzi Arif Lubis; Nurul Inayah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The purpose of this study is to identify the factors that cause the rejection of customer claims by insurance companies. Insurance is a form of protection or contract between the insured and the insurer when the insured is required to pay premiums or contributions to the insurance company, and the insurer has the full obligation to guarantee payment in the event of unexpected losses in accordance with the agreement that has been made. This research is qualitative research. This study focuses on the causes of claim rejection by insurance companies in Bumiputera Sharia Life Insurance. The results of this study determine that the cause of claim rejection affects the rejection of claims at Bumiputera Sharia Life Insurance.